2020
DOI: 10.1186/s13018-020-01886-1
|View full text |Cite
|
Sign up to set email alerts
|

Does arthroscopic repair show superiority over open repair of lateral ankle ligament for chronic lateral ankle instability: a systematic review and meta-analysis

Abstract: Background: There is still no definite consensus on whether arthroscopic repair shows superiority over open repair for chronic lateral ankle instability. We conducted a systematic review and meta-analysis of the current comparative studies to make a generalized analysis. Methods: PubMed, Embase, and Web of Science databases were searched from inception to April 2020. Included studies were assessed by the level of evidence and quality of evidence (Cochrane Handbook or MINORS). The process of data extraction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…4 Advancements with instruments and techniques in recent years have resulted in a higher spatial resolution for arthroscopic procedures compared with open ones. 2,17,19,20,26 These procedures were developed gradually from arthroscopy-assisted to all-inside arthroscopic techniques. Vega et al 23 reported that 16 patients with chronic lateral ankle instability were treated with an all-inside arthroscopic repair technique, with ankle stability restored in all cases without major complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Advancements with instruments and techniques in recent years have resulted in a higher spatial resolution for arthroscopic procedures compared with open ones. 2,17,19,20,26 These procedures were developed gradually from arthroscopy-assisted to all-inside arthroscopic techniques. Vega et al 23 reported that 16 patients with chronic lateral ankle instability were treated with an all-inside arthroscopic repair technique, with ankle stability restored in all cases without major complications.…”
Section: Discussionmentioning
confidence: 99%
“…Some series have indicated superior clinical results with arthroscopic techniques compared with open techniques and hold the potential to alleviate more pain due to the minimally invasive nature of the procedure. 1,20,21,26 However, compared with conventional open surgeries, arthroscopic procedures have more technological challenges and a higher complication risk. 1,16 For example, the risk of nerve entrapment is a primary concern.…”
mentioning
confidence: 99%
“…As endoscopic skill became more universal, the ability to perform this procedure with the arthroscope is possible and reproducible with less aggression to the patients. The short-term clinical outcomes are better, 29 with no significant difference in complication rate, 29 , 30 so we can predict that in the future the recommended method for surgical treatment of CAI will be arthroscopic.…”
Section: Lateral Instabilitymentioning
confidence: 98%
“…The modified Broström procedure (repair of the anterior talofibular ligament and augmentation with the inferior extensor retinaculum, Fig. 1 ) is a standard procedure for CLAI patients who do not respond to three to six months of conservative management [ 4 6 ]. Patients with OLTs less than 15 mm in diameter are usually treated with intra-articular debridement and microfracture [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%